PENURUNAN TINGKAT DEPRESI PADA PASIEN DENGAN GANGGUAN JIWA DI KABUPATEN LAMONGAN DENGAN TERAPI MINDFULNESS - Wibowo, Renata Febriyanti; Sholikhah, Siti; Rokhman, Abdul (Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of depression is currently increasing. Indonesia in East Java province is ranked 19th in cases of depression. The depression rate in Indonesia is 6.4%, around 20.8 million. This study aims to determine whether self-awareness therapy contributes to reducing the level of depression in patients with mental disorders at the Berkas Bersinar Abadi Foundation, Nguwok Village, Modo District, Lamongan Regency. Pre-experiment was used to design the study. This method uses a one-group pre-experiment-post-experiment design. The total number of samples used for the population was 34 people. The Beck Depression Inventory II (BDI-II) questionnaire was used to collect data for this study. After data tabulation, the Wilcoxon Sign Rank Test was used with a significance level of p=< 0.05. The results of the study showed that before being given therapy, the majority of patients who experienced depression before therapy had (61.8%) levels of severe depression, and after giving mindfulness therapy there were (38.2%) normal levels. The results of the Wilcoxon test show that there is an effect of mindfulness therapy on reducing depression with a value of p=0.000 where 0<0.005 means there is an effect of mindfulness therapy on reducing the level of depression in patients with mental disorders at the Lamongan Regency. Mentally disordered patients who are depressed should be given mindfulness therapy to make the patient feel calmer so that their depression can be reduced.